1999
DOI: 10.1056/nejm199906033402206
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alternative Medicine by Women with Early-Stage Breast Cancer

Abstract: Among women with newly diagnosed early-stage breast cancer who had been treated with standard therapies, new use of alternative medicine was a marker of greater psychosocial distress and worse quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
405
21
16

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(472 citation statements)
references
References 23 publications
30
405
21
16
Order By: Relevance
“…Interestingly, although inadequate physician-patient communication and dissatisfaction with some aspects of conventional health care may be contribut-ing factors to desperation, only two patients admitted that desperation was the reason for CAM use. A study by Burstein et al investigating breast cancer patients showed that those patients that were more depressed and had greater fear of recurrence were more prone to using CAM 17 . In our study, divorced patients used CAM signifi cantly more often than other groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although inadequate physician-patient communication and dissatisfaction with some aspects of conventional health care may be contribut-ing factors to desperation, only two patients admitted that desperation was the reason for CAM use. A study by Burstein et al investigating breast cancer patients showed that those patients that were more depressed and had greater fear of recurrence were more prone to using CAM 17 . In our study, divorced patients used CAM signifi cantly more often than other groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of CM was associated with a greater number of physical symptoms and with symptoms of a greater intensity (Burstein, Gelber, Guadagnoli, & Weeks, 1999). Assessing an individual's illness profile is therefore an important part of understanding his or her motivations to use complementary medicine.…”
Section: Illness Profiles and CM Usementioning
confidence: 99%
“…1,7,[15][16][17][18][19][20][21][22] Indeed in our study, women who agreed to participate in the adjunctive studies were more Table 3 Psychological test scores between women who agreed or did not agree to adjunctive experimental therapy 5,19 emotional characteristics may be as, or more, important. These emotional characteristics included need for control of therapy, 17 psychological factors, [18][19][20] and feelings of being coerced into specific treatments.…”
Section: Discussionmentioning
confidence: 83%
“…21 Users of alternative therapy felt unhappy with the medical information and care they received, 18 had a higher incidence of somatization disorders, 19 experienced more hopelessness, 20 and were psychologically more labile with high anxiety and depression. 1 Our study has several important limitations, including the small number of patients (42 women) and the retrospective nature of the study. However, as a pilot study it suggests that decision-making, even within a medical setting, may relate to psychological distress as much as to cognitive decision-making.…”
Section: Discussionmentioning
confidence: 95%